Essentiality Of The Project Manager In Project Management Practice In Housing Development: A Case Study In Penang - Chan, Han Pin (2008)
Housing industry has a great contribution to the national growth and it forms part of the productive economic sector and contributes to our country Gross Domestic Product (GDP). Government has taken a lot of initiative in housing provision and introduce various policies and incentives to help the private sector in housing development and housing provision for purchaser from all income level. However, current threat and challenge has build up the barrier that slow down the industry growth.